2019
DOI: 10.24251/hicss.2019.708
|View full text |Cite
|
Sign up to set email alerts
|

Analytics Use Cases for Mass Customization – A Process-based Approach for Systematic Discovery

Abstract: Nowadays, mass customization (MC) is shaped by the application of digital technologies like computeraided design, computer aided manufacturing, and distribution planning. Within a MC process, various data is created, which can be used to gain knowledge about past and future business activities by means of modern data analytics methods. The paper at hand applies design science research and presents a process-based approach for identifying potential analytics use cases for MC. For this purpose, a generic MC proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Although the information gathered from the interviews indicated that the companies expected rapid solutions to complex problems from IT support, the response to the proposal to introduce analytics was cautious. Therefore, we used a method to identify analytics use cases [37]. We analyzed each phase of the network VCC process with each company and derived implementable use cases for data analytics.…”
Section: Analytics Systemmentioning
confidence: 99%
“…Although the information gathered from the interviews indicated that the companies expected rapid solutions to complex problems from IT support, the response to the proposal to introduce analytics was cautious. Therefore, we used a method to identify analytics use cases [37]. We analyzed each phase of the network VCC process with each company and derived implementable use cases for data analytics.…”
Section: Analytics Systemmentioning
confidence: 99%